2008
DOI: 10.1002/pon.1397
|View full text |Cite
|
Sign up to set email alerts
|

A visual approach to providing prognostic information to parents of children with retinoblastoma

Abstract: Provision of information at diagnosis concerning long-term treatment complexity helps parents of children with cancer. DePICT effectively transfers knowledge of treatments, risks, and prognosis in a manner that offsets parental educational disadvantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
17
0
5
Order By: Relevance
“…10 Methods used to communicate with patients in developed countries such as graphic tools and electronic multimedia-based programs may not be applicable to indigent populations in the developing world. 11,12 In addition, written pamphlets and electronic programs can be prohibitively expensive in financially limited clinics. We aimed to determine whether a poster presentation combined with a verbal informed consent would be an effective means for educating cataract patients in rural South India.…”
mentioning
confidence: 99%
“…10 Methods used to communicate with patients in developed countries such as graphic tools and electronic multimedia-based programs may not be applicable to indigent populations in the developing world. 11,12 In addition, written pamphlets and electronic programs can be prohibitively expensive in financially limited clinics. We aimed to determine whether a poster presentation combined with a verbal informed consent would be an effective means for educating cataract patients in rural South India.…”
mentioning
confidence: 99%
“…Based on our previous study demonstrating a mean comprehension score of 86% (95% confidence interval [CI] 81.3-90.6), 11 it was estimated that with increased complexity of the design the mean comprehension score would be 80%. A sample size of 39 patients completing the task would provide a power of 0.80 and 95% CI.…”
Section: Sample Size and Data Analysesmentioning
confidence: 99%
“…[8][9][10] Therefore, our group developed a visual tool named Diseasespecific electronic Patient Illustrated Clinical Timelines (DePICT) that summarizes treatment histories of patients with retinoblastoma for clinicians to access point-of-care information and has been validated among parents in a previous study. 11 The study demonstrated that parents of patients with retinoblastoma were able to interpret timelines for treatment of 1 eye with retinoblastoma achieving a mean comprehension score of 86%. However, the study did not distinguish between unilateral and bilateral disease, and evaluated understanding of treatment choices pertaining to 1 eye instead of 2 eyes at once.…”
mentioning
confidence: 97%
“…Due to the early age of Rb diagnosis, parents become the primary decisions makers and therefore, seek an active advocacy role in their child's health care needs [54]. Confronted with information that is difficult to digest and poorly communicated, such as treatment options, risks and outcomes, parents can become easily overwhelmed and misunderstand what is being asked of them.…”
Section: The Parentsmentioning
confidence: 99%
“…Confronted with information that is difficult to digest and poorly communicated, such as treatment options, risks and outcomes, parents can become easily overwhelmed and misunderstand what is being asked of them. This can sometimes result in delayed treatment decisions that may put the child at a disadvantage [54]. General and disease-specific information that is presented at a level each parent is able to understand, improves parental adjustment, increases their understanding of risk, and potentially improves outcomes and compliance with treatment [55].…”
Section: The Parentsmentioning
confidence: 99%